Local forest management: the impacts of devolution policies - Edmunds, D.; Wollenberg, Eva Karoline (Routledge, 2003)
Local government is built around careful and illuminating case studies of the effects of devolution policies on the management of forests in several Asian countries. The studies demonstrate that devolution policies - contrary to the claims of governments - have actually increased governmental control over the management of local resources, and a lower cost to the state. The controversial findings show that if local forest users are to exercise genuine control over forest management, they must be better represented in the processes of forming, implementing and evaluating devolution policies. In addition, the guiding principle for policy discussions should be to create sustainable livelihoods for local resource users, especially the poorest among them, rather than reducing the cost of government forest administration.